1999
DOI: 10.1093/ndt/14.6.1418
|View full text |Cite
|
Sign up to set email alerts
|

Anti-DNA antibodies in the urine of lupus nephritis patients

Abstract: It is suggested that the failure to detect anti-DNA antibodies in the urine in the previous work was due to failure to inhibit the endogenous urinary DNase. It remains to be determined whether the retention of anti-DNA antibodies or excessive secretion is correlated with clinical phases of LN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
4
5
0
Order By: Relevance
“…A similar pattern of decrease in serum autoantibody titers has been reported for antiphospholipid antibodies at the time of thrombosis (34) and for anti-Ro in congenital heart block (35). However, an alternative explanation is that anti-dsDNA is lost in the urine during renal flares (36,37). In a recent study of 20 SLE nephritis patients, the amount of anti-dsDNA in the urine was equal to the expected leakage, based on calculations using antidsDNA and total immunoglobulin levels in serum and urine (i.e., there was neither specific entrapment nor excretion of anti-dsDNA) (36).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A similar pattern of decrease in serum autoantibody titers has been reported for antiphospholipid antibodies at the time of thrombosis (34) and for anti-Ro in congenital heart block (35). However, an alternative explanation is that anti-dsDNA is lost in the urine during renal flares (36,37). In a recent study of 20 SLE nephritis patients, the amount of anti-dsDNA in the urine was equal to the expected leakage, based on calculations using antidsDNA and total immunoglobulin levels in serum and urine (i.e., there was neither specific entrapment nor excretion of anti-dsDNA) (36).…”
Section: Discussionsupporting
confidence: 67%
“…However, an alternative explanation is that anti-dsDNA is lost in the urine during renal flares (36,37). In a recent study of 20 SLE nephritis patients, the amount of anti-dsDNA in the urine was equal to the expected leakage, based on calculations using antidsDNA and total immunoglobulin levels in serum and urine (i.e., there was neither specific entrapment nor excretion of anti-dsDNA) (36). For renal flares, our study cannot differentiate between the possibility that deposition of anti-dsDNA in the kidneys led to an increase in proteinuria versus the possibility that an increase in proteinuria led to a loss of anti-dsDNA in the urine.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is also supported by the experimental work of others in that higher concentrations of extracellular DNA (especially larger DNA fragments) facilitate the clearance of anti-dsDNA from circulation (42,43). There is even speculation that autoantibody levels may drop as a direct result of proteinuria (72). Therefore, we speculate that, by blocking NET formation, we are reducing the nidus of extracellular DNA available for immune complex formation and deposition.…”
Section: Discussionsupporting
confidence: 63%
“…However, some studies have found that anti-dsDNA levels drop in flare-up of the disease [7,35] Another study did not find a relationship between elevated anti-dsDNA levels and flares [23]. The development of nephrotic syndrome in some SLE patients is accompanied by lowering levels of anti-dsDNA-antibodies [36]. Furthermore, it has been reported that titers of the anti-dsDNA-antibodies decreased in NZM lupus nephritis mice when immune complex deposition accelerated and proteinuria developed [37].…”
Section: Discussionmentioning
confidence: 99%